Features of antihypertensive therapy in the Russian population: data from the ESSE-RF3 study - Yu. A. Balanova; S. A. Shalnova; V. A. Kutsenko; A. E. Imaeva; O. E. Ivlev; S. E. Evstifeeva; A. V. Kapustina; M. B. Kotova; S. A. Maksimov; G. A. Muromtseva; T. V. Repkina; T. O. Gonoshilova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the usage of antihypertensive drugs (AHDs) and their combinations in participants aged 35 to74 years with arterial hypertension (AH) in the population-based study ESSE-RF3.Material and methods. Representative samples of the population aged 35 to 74 years from 15 regions of Russia (n=28731) with a response rate over 70% were examined in the ESSE-RF3 study. Therapy received by 9944 participants with AH (with systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg, or when the subject was taking AHDs) was analyzed. Information about AHDs intake (brand name of the drug) was recorded by questionnaire and coded according to International Nonproprietary Names by classes. Statistical analysis was performed using the open-source R 4.1 environment. Comparison of discrete indicators between groups was performed using Fisher’s exact test. The significance level for all tested hypotheses was taken as.05. The study was approved by the Ethics Committee of FGBI “NMRC TPM” of the Ministry of Health of the Russian Federation, each participant signed an informed consent.Results. Among the patients receiving therapy for AH, angiotensin-converting enzyme inhibitors (ACEIs) were used by 38.8% of participants, angiotensin receptor blockers (ARBs) — 31.6%, betablockers (BBs) — 29.0%, сalcium channel blockers (CCBs) — 21.5%, diuretics — 18.6%, 1.1% — outdated AHDs; 8.6% — other groups of drugs. Monotherapy was used by 53.1% of patients, 33.1% of participants received two, and 13.9% received three AHDs. Among participants taking two or more AHDs (including single-pill combinations (SPC)), males most often received the combination of BB+ ACEI and females — BB+ARBs. SPC AHDs were used by 10.3% of those receiving therapy (males: 9.8%, females: 10.6%). Among SPCs, the top three combinations were CCBs + ACEIs (28%), diuretics + ACEIs (27.5%), and diuretics + ARBs (24.4%).Conclusion. The population study ESSE-RF3, based on the survey of a representative sample of the Russian population aged 35-74 years, showed that more than a half of participants with AH receiving therapy were used the monotherapy, only every tenth of those treated received SPC. The problem of insufficient patients’ literacy was indicated — about 1% of patients received outdated AGPs. In addition, 8.6% of patients used non-AHDs for the treatment of AH. For improving the control of AH treatment, it is necessary to increase the adherence of patients to the prescribed therapy and more strict adherence of doctors to the published guidelines for AH treatment.